MULTIVARIATE MAGNETIC FIELD ANALYSIS AND LEVITATION FORCE CALCULATION OF THE ACTIVE AXIAL MAGNETIC BEARING (AAMB) - Graca, Piotr; Tomczuk, Bronisław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The paper presents multivariate calculations of magnetic field and magnetic force in the active axial magnetic bearing actuator (AAMB). The field model has been developed using Finite Element Method (FEM) and has been used for AAMB construction analysis. As a result of multivariate calculations the beneficial dimensions of a bearing disk were determined, where the electromagnet dimensions were used as a reference.